Hubungan status gizi dengan kejadian anemia pada ibu hamil di Puskesmas Kotagede II Yogyakarta - Larasajeng Permata Sari; Sarwinanti Sarwinanti; Sittti Nur Djannah (Universitas Ahmad Dahlan, 2020)
Maternal deaths in Yogyakarta Special Region are caused by heart disease, bleeding, eclampsia, sepsis/infection. Bleeding is still the number one cause of maternal death. Pregnancy with anaemia is 5 times more at risk of bleeding than those who are not. The aims of the research are to determine the relationship of nutritional status with anaemia in pregnant women in Kotagede II Yogyakarta Public Health Center. This was an observational analytic design and a cross-sectional approach. The sampling method uses an accidental sampling technique. The number of respondents was 77 pregnant women in the second and third trimesters. The research instrument used questionnaire sheets and medical records. Data were processed by Chi-Square statistical tests. Study found (p-value) of nutritional status = 0.001. The conclusion of this study is that there was a significant relationship between nutritional status with the incidence of anaemia at Kotagede II Yogyakarta Health Center.